KENDALA DALAM MEWUJUDKAN KINERJA - Nynda Salsabylah; Haidar Ahmad; Adi Lukman Hakim (STKIP Subang, 2025)
Human resource performance (HR performance) is a strategic factor that determines the effectiveness of public organizations. This study aims to analyze the performance level and the influencing factors among government employees in Lamongan Regency. The research applies a quantitative descriptive-associative approach with a total sample of 39 employees. The independent variables include ability, motivation, discipline, and responsibility, while the dependent variable is HR performance. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, correlation analysis, and multiple linear regression. The results indicate that the instruments are valid and reliable (Cronbach’s Alpha = 0.882). The average HR performance score is 4.21, categorized as high. The four independent variables have a positive and significant influence on HR performance (R² = 0.724; Sig F = 0.000), with responsibility emerging as the most dominant factor (β = 0.341; Sig = 0.000). These findings highlight the importance of enhancing employees’ responsibility and motivation to strengthen performance within the public sector.